AFTER EARTHQUAKE IN SIGI: CAN SOCIAL SUPPORT AFFECT CAREER DECISION SELF-EFFICACY? - Salim, Rose Mini Agoes; Darmayanti, Kusumasari Kartika Hima (Jurnal Cakrawala Pendidikan, 2021)
An earthquake struck Central Sulawesi Province, Indonesia in 2019, and Sigi Regency was one of the most affected areas. Based on a psychological perspective, studies were significant to understand how earthquakes impacted Post-Traumatic Stress Disorder. This study aimed to examine the effect of social support on CDSE (Career Decision Self-Efficacy). As many as 141 high school students as the earthquake victims in Sigi filled out the Career Decision-Making Self-Efficacy Scale Short-Form (CDMSES-SF) and Adolescent Social Support Scale (ASSS). The data were analyzed using the multiple regression approach in IBM SPSS Software Version 23.00. The findings showed that teachers’ social support successfully enhanced CDSE. Also, CDSE was significantly affected by social support received from peers. On the other hand, this study confirmed that there was no significant effect of parents’ social support on CDSE. The results contributed to the career counseling program for high school students by taking into account teachers’ and peers’ social support.